2016
DOI: 10.1080/2162402x.2016.1207032
|View full text |Cite
|
Sign up to set email alerts
|

Addition of anti-estrogen therapy to anti-HER2 dendritic cell vaccination improves regional nodal immune response and pathologic complete response rate in patients with ERpos/HER2posearly breast cancer

Abstract: HER2-directed therapies are less effective in patients with ER compared to ER breast cancer, possibly reflecting bidirectional activation between HER2 and estrogen signaling pathways. We investigated dual blockade using anti-HER2 vaccination and anti-estrogen therapy in HER2/ER early breast cancer patients. In pre-clinical studies of HER2 breast cancer cell lines, ER cells were partially resistant to CD4 Th1 cytokine-induced metabolic suppression compared with ER cells. The addition of anti-estrogen treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 41 publications
0
17
0
1
Order By: Relevance
“…This observation prompted a new clinical trial where a brief course of anti-estrogen therapy was supplied to ER pos DCIS subjects concurrent with vaccination. In this second trial, pCRs of ER pos subjects increased from 5% to about 30% such that their rates were now no longer statistically different from their ER neg counterparts [9]. This study showed that combining vaccination with small molecule drugs capable of inhibiting signaling pathways associated with maintenance of an oncogenic phenotype could dramatically enhance clinical response rates.…”
Section: Research Papermentioning
confidence: 72%
“…This observation prompted a new clinical trial where a brief course of anti-estrogen therapy was supplied to ER pos DCIS subjects concurrent with vaccination. In this second trial, pCRs of ER pos subjects increased from 5% to about 30% such that their rates were now no longer statistically different from their ER neg counterparts [9]. This study showed that combining vaccination with small molecule drugs capable of inhibiting signaling pathways associated with maintenance of an oncogenic phenotype could dramatically enhance clinical response rates.…”
Section: Research Papermentioning
confidence: 72%
“…Datta et al reported that a preserved anti-HER2 Th1 response was associated with pCR to neoadjuvant trastzumab application combined with chemotherapy ( 70 ). In addition, the anti-HER2 DC vaccination was combined with anti-estrogen therapy which improved regional nodal immune response and pCR rate in patients with estrogen receptor + /HER2 + early breast cancer ( 71 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Czerniecki et al showed anti-HER2 CD4 + Th1 immunity to be a relevant component of HER2 + therapy, as loss of CD4 + Th1 responses correlated with poor prognosis and treatment responses 15 . The administration of a class II HER2 peptide-pulsed Type I polarized DC1 vaccine was shown to induce a strong anti-HER2 CD4 + Th1 response, with a pathologic complete response rate (pCR) among HER2 + ductal carcinoma in situ (DCIS) patients [69][70][71] .…”
Section: Immune Checkpoint Inhibitorsmentioning
confidence: 99%